Post-COVID-19 resurgence of scabies’ cases in the Lazio Region, Italy: a new emerging public health threat? - Martina Spaziante; Alessandro Agresta; Maurizio D’Amato; Gabriella De Carli; Gilda Tonziello; Valentina Vantaggio; Giorgio Nicolò Malatesta; Enrico Girardi; Alessandra Barca; Paola Scognamiglio; Francesco Vairo (Infectious Diseases of Poverty)
Abstract Scabies represents a global health issue and in 2017 was added to the World Health Organization’s list of neglected tropical diseases. In European and Middle Eastern countries, cases are sporadic while recent surveillance data have pointed out an increasing incidence among vulnerable populations. Regional cases for Lazio, Italy, reported from 2017 to 2023 to the national infectious disease surveillance system were analyzed. In Lazio, just after the coronavirus disease 2019 (COVID-19) pandemic onset, a significant and immediate reduction in the incidence of scabies was recorded (− 79.6%) followed by a progressive and relevant increase (143.4% from 2020 to 2021, 142.3% from 2021 to 2022 and 170.3% from 2022 to 2023). Consistently, the number of scabies outbreaks, after a decrease following the first COVID-19 wave, has progressively increased over time, mainly due to the occurrence of outbreaks in long term facilities (750% from 2020 to 2023). The increased incidence may also be driven by the “pseudo-resistance” phenomenon (under dosed/early-discontinued treatment, suboptimal adherence, reduced drug bioavailability), but also by reduced in-vitro susceptibility to the mainly used scabicides. The rapidly evolving epidemiology of scabies in our country, as documented also in other regions, calls for a comprehensive approach to effectively address the problem.